Normal mRNA content in a phosphoglycerate kinase variant with severe enzyme deficiency. - Tani, K (1985)
A phosphoglycerate kinase variant, PGK-Matsue, was associated with a severe enzyme deficiency, congenital nonspherocytic hemolytic anemia, and mental disorders. The variant enzyme exhibited a slower cathodal electrophoretic mobility and lower affinity toward the substrates. The enzyme activity in the variant's red cells, muscles, and fibroblasts was about 5% of that of normal cells. The content of mRNA in the variant fibroblasts was compared to that of normal cells by the semiquantitative dot hybridization method, and, more accurately, by the liquid hybridization method, using a human PGK cDNA as a probe. It was found that the mRNA level in the variant fibroblasts was comparable to that of normal fibroblasts. The results strongly suggest that the major cause of enzyme deficiency in PGK-Matsue is a seven- to 10-fold increase in the mutant enzyme degradation.